Robust H-infinity control of two novel MEMS force sensors. (28th September 2020) - Obilikpa, S C
Abstract: This paper presents the design and implementation of a robust H-infinity controller on two novel MEMS force sensors. The novel microelectromechanical system (MEMS) sensors incorporated a mechanism that permits tuning of the device's mechanical stiffness and has been used for the characterization of micro-cantilever and biological tissues. To ensure stability and guaranteed performances, certain specifications such as error tracking, command moderation, disturbance rejection, and robustness in presence of uncertainties, were made and the H-infinity control technique was employed to synthesize robust controllers for the two force sensors. Finally, this robust controller, integral, and PID controllers were implemented on the real systems and their performance in closed-loop were compared.